Charge carrier injection and extraction of colloidal quantum dot assemblies: a perspective for optoelectronic devices - Satria Zulkarnaen Bisri (Journal of Information Display)
Efficient charge injection and transport are fundamental challenges in colloidal quantum dots (CQD) optoelectronic devices such as photodetectors, solar cells, and displays. Unlike traditional semiconductors, charge transport in QD films is governed by hopping mechanisms, influenced by interdot coupling, ligand chemistry, and defect states. However, many aspects of these processes remain poorly understood. The interplay between charge injection, interfacial trap states, and carrier mobility introduces complex loss pathways that hinder performance. Many key unanswered questions remain, including the influence of different QD compositions, ligand environments, and orders near the interface on charge transport. Here, we discuss the challenges that should be investigated and solved in the near future. Addressing these knowledge gaps through advanced spectroscopy, transport studies, and interfacial engineering will be crucial for unlocking the full potential of CQD for transport-based optoelectronic devices, including electroluminescence displays, paving the way for high-efficiency, low-power, and long-lifetime devices.